Effectiveness of the low power laser as adjuvant therapy in patients with zoster herpes - Haydée Revilla Arias; Yamila Valiente Hernández (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The low power laser has a wide use in the current medical practice.  There is a great number of patients with acute or chronic conditions that can be treated with this therapy, with encouraging results, far better than those obtained with the use of conventional therapy.  Objective: To evaluate the effectiveness of low power laser as adjuvant therapy to reduce the response time to pain relief in patients with zoster herpes. Methods: A quasi-experiment study of therapeutic intervention was carried out in 21 patients with zoster herpes. They were assisted in the Physical Medicine Service of the MININT Polyclinic in Santiago de Cuba, from January, 2016 to June, 2017. Two groups were conformed at random: the members of the first one received acyclovir, vitamins and lasertherapy (intervention); those of the second group received acyclovir, vitamins and analgesic (control). Results: It was observed that in the intervention group the intensity of the pain was diminishing in connection with the initial evaluation. This way, in the fifth session it was appreciated a higher percentage of patients with pain relief  that in the control group, the same as in the tenth session and 21 days later, hence the effectiveness of the treatment.   Conclusions: With the use of low power laser the patients with zoster herpes presented an improvement of the pain in less time, with a satisfactory response expressed in all of them, reason why its use is recommended as adjuvant therapy.